Cell cycle arrest and cell death correlate with the extent of ischaemia and reperfusion injury in patients following kidney transplantation – results of an observational pilot study. (30th March 2018) - Schmitt, Felix C. F.; Salgado, Eduardo; Friebe, Janina; Schmoch, Thomas; Uhle, Florian; Fleming, Thomas; Zemva, Johanna; Kihm, Lars; Nusshag, Christian; Morath, Christian; Zeier, Martin; Bruckner, Thomas; et al.
Summary: A prolonged cold ischaemia time (CIT) is suspected to be associated with an increased ischaemia and reperfusion injury (IRI) resulting in an increased damage to the graft. In total, 91 patients were evaluated for a delayed graft function within 7 days after kidney transplantation (48 deceased, 43 living donors). Blood and urine samples were collected before, immediately after the operation, and 1, 3, 5, 7 and 10 days later. Plasma and/or urine levels of total keratin 18 (total K18), caspase‐cleaved keratin 18 (cc K18), the soluble receptor for advanced glycation end products (sRAGE), tissue inhibitor of metalloproteinase‐2 (TIMP‐2) and insulin‐like growth factor‐binding protein‐7 (IGFBP7) were measured. As a result of prolonged CIT and increased IRI, deceased donor transplantations were shown to suffer from a more distinct cell cycle arrest and necrotic cell death. Plasmatic total K18 and urinary TIMP‐2 and IGFBP7 were therefore demonstrated to be of value for the detection of a delayed graft function (DGF), as they improved the diagnostic performance of a routinely used clinical scoring system. Plasmatic total K18 and urinary TIMP‐2 and IGFBP7 measurements are potentially suitable for early identification of patients at high risk for a DGF following kidney transplantation from deceased or living donors.